"Advertisements of Every Kind to Bring Their Brand into Notoriety": Branding and "Brandolatry" in the Nineteenth-Century Champagne Trade in Britain*. (20th November 2017) - Harding, Graham
Abstract: This paper examines the branding and marketing techniques used to develop the British champagne market in the nineteenth century. It draws upon the archives of the major French champagne houses and the extensive collection of price lists and marketing material in the scattered archives of W. & A. Gilbey, the dominant wine distributor in nineteenth-century Britain, to focus on the period from 1850 to the early 1900s. This period saw the creation of a powerful marketing template centered on a group of premium brands that endured for well over a century and influenced champagne marketing worldwide. Contemporary commentators saw a "cult" of famous brands, which disadvantaged consumers and merchants. Looking back at this period through the lens of a century of marketing history, we can clearly see a different picture: one of astute marketing (although that term was not then in use) that exploited selective distribution and created the concept of vintage-dated wine (what we would today call "limited-edition" product lines), making the champagne houses and their agents early exponents of Jean-Noël Kapferer's twenty-first-century "anti-laws" of luxury marketing. (JEL Classification: M3)